Diagnostic Laparoscopy and Endometriosis - Chalermchockcharoenkit, Amphan; Techatraisak, Kitirat (Siriraj Medical Journal, 2020)
The prevalence of endometriosis in the population varies according to the study. The purpose of this paper is to determine and evaluate the frequency of endometriosis in patients who underwent diagnostic laparoscopy with various clinical diagnoses and presentations. Medical and laparoscopic surgical records of 856 patients who underwent diagnostic laparoscopy from January 1999 to December 2000 in the Endoscopic Unit, Department of Obstetrics and Gynecology, Siriraj Hospital, are retrospectively evaluated. 661 consecutive cases aged from 17-71 years were recruited for the study. 51.1% were finally diagnosed with endometriosis and the majority were between 20-39 year-old. We found 194 endometriotic cases out of 229 clinically suspected endometriotic cases (84.7%), 50 out of 84 pre-operative chronic pelvic pain cases (59.5%), and 52 out of 132 infertility cases (39.4%). However, no visible pathology was detected in 13 out of 229 clinically suspected endometriotic cases (5.7%). Interestingly, among endometriotic cases in the chronic pelvic pain group, 36 cases (72.0%) had a minimal to mild degree of endometriosis while 14 cases had a moderate to severe degree. For all clinical diagnoses, the frequency of endometriosis in patients with an adnexal mass was found to be significantly higher than that without adnexal mass, 125 /171 cases (73.1%) compared with 181 /368 (49.2%) respectively (p < 0.05). We conclude from this study that the revised ASRM system of classifying endometriosis has limitations and inherent defects. This system does not correlate well with pain. However, at the time of laparoscopy, endometriosis should be staged according to the revised ASRM classification of endometriosis in order to facilitate follow-up and comparison if future surgery is performed. To avoid unnecessary exposure to the attendant risks and the expense of laparoscopy, most diagnostic laparoscopies should be performed selectively. Biopsy is recommended in any clinically suspected endometriosis.